Supercritical CO2-assisted processes for development of added-value materials: Optimization of starch aerogels preparation and hemp seed extracts impregnation. (July 2022) - Lukic, Ivana; Pajnik, Jelena; Tadic, Vanja; Milovanovic, Stoja
Abstract: The aim of the present study was the utilization of supercritical CO2 as a green medium in various processes: starch gel drying, supercritical extraction from hemp seed flour (SCE process), hemp seed oil (HSO) impregnation (SCI process), as well as integrated process of hemp seed flour (HSF) extraction and starch gels impregnation (SCE-SCI process) for development of added-value materials that can be used as phytopharmaceuticals. Optimization of starch aerogels was performed by variation of temperature (35 and 45 °C) and pressure (8, 10, and 20 MPa) in order to obtain materials with high porosity, which will enable maximal loading capacity for hemp seed extracts. Proposed scCO2 -assisted processes of SCE from HSF, SCI and SCE-SCI were performed at pressure of 30 MPa and temperature of 60 °C. It was shown that conditions of starch gel drying significantly influenced material morphology (porosity was in a range of 48–82%, and specific surface area of 71–208 m 2 /g), which consequently determined aerogel loading capacity. FTIR analysis confirmed that scCO2 did not have effect on polymer composition nor it remained in polymer after drying process. The highest loading of both HSO and HSF extract (24.9% and 29.78%, respectively) was achieved when aerogel obtained at 10 MPa and 45 °C was tested as a carrier. Furthermore, chemical analysis showed that both HSO and HSF extract are rich in unsaturated fatty acids especially linoleic acid (54–59%) and α-linolenic acid (15–18%). These essential fatty acids have well-established health benefits including protection against cardiovascular, neurodegenerative and inflammatory diseases. Graphical Abstract: ga1 Highlights: scCO2 drying process condition significantly influenced morphology of starch aerogels. scCO2 extraction of hemp seed flour enabled yield of up to 11.6%. The highest loading of hemp seed extracts was achieved in aerogels dried at 10 MPa and 45 °C. Hemp seed oil and flour extract are mainly composed of unsaturated fatty acids (~90%).